Faktor-Faktor yang Berhubungan dengan Kejadian Stunting di Desa Aik Dewa Wilayah Kerja Puskesmas Pringgasela Utama - Fibrianti; Sari, Jusmala (STIKes Hamzar, 2022)
Background: Stunting is a chronic malnutrition problem caused by a lack of nutritional intake for a long time, this causes future problems, namely experiencing difficulties in achieving optimal physical and cognitive development and to find out factors related to the incidence of stunting in Aik Dewa Village, the working area of ​​the Pringgasela Utama Health Center in 2022. Methods: This research method is a quantitative study, with a cross-sectional design approach. The population in this study were all mothers who had stunted toddlers aged 24-59 months, totaling 20 people during February 2022 in Aik Dewa Village, Pringgasela Utama Health Center Working Area, using Total Sampling. The independent variables in this study were age of marriage, history of exclusive breastfeeding, and history of LBW. The dependent variable in this study is the incidence of stunting. The data analysis used is univariate and bivariate. Results: The results showed that there was a relationship between history of exclusive breastfeeding (p-value 0.002), history of LBW (p-value 0.00), age at marriage (p-value 0.005) and stunting. Conclusion: There is a relationship between a history of exclusive breastfeeding, a history of LBW and a history of age at marriage with the incidence of stunting in Aik Dewa Village, the working area of ​​the Pringgasela Utama Health Center in 2022.